Increased HDAC Activity and c-MYC Expression Mediate Acquired Resistance to WEE1 Inhibition in Acute Leukemia - Garcia, Tamara B.; Uluisik, Rizvan C.; van Linden, Annemie A.; Jones, Kenneth L.; Venkataraman, Sujatha; Vibhakar, Rajeev; Porter, Christopher C. (Frontiers in Oncology, 2020)
WEE1 is a cell cycle and DNA damage response kinase that is emerging as a therapeutic target for cancer. AZD1775 is a small molecule inhibitor of WEE1, currently in early phase clinical trials as a single agent and in combination with more conventional anti-neoplastic agents. As resistance to kinase inhibitors is frequent, we sought to identify mechanisms of resistance to WEE1 inhibition in acute leukemia. We found that AZD1775 resistant cell lines are dependent upon increased HDAC activity for their survival, in part due to increased KDM5A activity. In addition, gene expression analyses demonstrate HDAC dependent increase in MYC expression and c-MYC activity in AZD1775 treated resistant cells. Overexpression of c-MYC confers resistance to AZD1775 in cell lines with low base line expression. Pharmacologic inhibition of BRD4, and thereby c-MYC, partially abrogated resistance to AZD1775. Thus, acquired resistance to WEE1 inhibition may be reversed by HDAC or BRD4 inhibition in leukemia cells.